SPLENIC PROTECTIVE EFFECT OF WHITE TURMERIC EXTRACT AGAINST COPPER TOXICITY IN MALE WISTAR RATS - CHIUMAN, LINDA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: This study was aimed to investigate the protective effect of white turmeric against copper splenic toxicity in male Wistar rats. Methods: This study used 30 rats divided into six groups: Negative groups, positive groups, Ethanol Extract of White Turmeric I-III. After 14 days, all rats were sacrificed by chloroform inhalation, and the spleen was excised and process to histopathology preparation and evaluation. Results: The result of this study showed that white turmeric acutely protected spleen from the impact of copper by reducing congestion/vasodilatation of the blood vessel (p=0.002), neutrophil infiltration (p<0.05), and lymphoid necrosis (p<0.05). Nevertheless, white turmeric extract may induce chronic inflammation by increasing the number of macrophage cells (p=0.003). Conclusion: Overall, it can be concluded that the white turmeric extracts acutely protect spleen from the impact of copper.